The Effect of Work-Family Conflict, Workload, Non-Financial Compensation and Job Stress on Employee Turnover Intention at PT Herba Emas Wahidatama Purbalingga - Melina Nur Afifah; Hermin Endratno; Suyoto; Totok Haryanto (Indonesian Journal of Business Analytics, 2024)
This study examines the influence of Work-Family Conflict, Workload, Non-Financial Compensation, and Employee Work Stress on Employee Turnover Intention at PT Herba Emas Wahidatama Purbalingga. This study uses primary data and is a type of quantitative research. Employees at PT Herba Emas Wahidatama Purbalingga, with a population of 160 people, using a purposive sampling method with a minimum service period of 1 year. The analysis test in this study are using multiple regression analysis through the SPSS 26 application. The results of this study indicate that Non-Financial Compensation and job stress have a positive and significant effect on Turnover Intention. However, Work-Family Conflict and Workload have no impact on Turnover Intention